2022
DOI: 10.1002/cpe.7224
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the language of depression from multivariate twitter data using a feature‐rich hybrid deep learning model

Abstract: Depression is a clinical entity that might be difficult for a psychiatrist to diagnose it effectively on time. A depressed person usually suffers from distress and anxiety, leading to serious consequences if not diagnosed early. Social media platforms facilitate users to exchange ideas and dialogs, resulting in the collection of a huge volume of data. Analyzing user's online behavior to categorize depression is a challenging task for researchers. This motivated researchers to investigate machine learning, deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The results showed that deep learning is more accurate in identifying DD and its risk factors compared to traditional machine learning by ranking the key factors of veterans and capturing the hidden pattern multilayer network structure in the data to obtain better classification performances. Kour et al [49] combined feature extraction techniques and a hybrid deep learning model of CNN-LSTM for depression classification and compared it with four traditional machine learning models for efficiency comparison, and showed that the recognition accuracy on the benchmark dataset reached 96.78%, which is better than the state-of-the-art traditional machine learning techniques. Deep learning, with its technological advantages, has a stronger predictive ability in DD diagnosis [50]; therefore, this study advocates for the use of deep learning algorithms for the automatic diagnosis of DD.…”
Section: Frontal Six-channel Eeg Signals Combined With Deep Learning ...mentioning
confidence: 99%
“…The results showed that deep learning is more accurate in identifying DD and its risk factors compared to traditional machine learning by ranking the key factors of veterans and capturing the hidden pattern multilayer network structure in the data to obtain better classification performances. Kour et al [49] combined feature extraction techniques and a hybrid deep learning model of CNN-LSTM for depression classification and compared it with four traditional machine learning models for efficiency comparison, and showed that the recognition accuracy on the benchmark dataset reached 96.78%, which is better than the state-of-the-art traditional machine learning techniques. Deep learning, with its technological advantages, has a stronger predictive ability in DD diagnosis [50]; therefore, this study advocates for the use of deep learning algorithms for the automatic diagnosis of DD.…”
Section: Frontal Six-channel Eeg Signals Combined With Deep Learning ...mentioning
confidence: 99%
“…It is well acknowledged that language use and language processing are highly reflective of individual differences in personality traits [8][9][10][11][12], gender [11], mood [13,14], stance detection [15][16][17], and demographic characteristics [18][19][20][21]). Differences in language use and processing have further proved to be effective markers of psychiatric symptoms, particularly in the case of depression [22][23][24][25], where even the most conservative classification models perform comparably to the standard of validated self-report scales of symptom severity [24] and clinical assessment [22]. This suggests that language features capture a substantial portion of depression symptom variance.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in mental health, predictive models have successfully been applied [12,63]. Exemplary contributions include the detection of depression [29], suicidal mental tendencies [21], bipolar disorders [24] and other mental disorders [20]. Moreover, the models proposed by [38] can uncover patterns of anorexia in datasets obtained from social networks.…”
Section: Introductionmentioning
confidence: 99%